The battle for Islam - Jenkins, Paul; Sardar, Ziauddin; BBC Education & Training ([S.l.] : BBC Active, 2006)
A far-reaching exploration of Islam after 9/11, this program follows renowned scholar Ziauddin Sardar on an eye-opening journey through Morocco, Turkey, Pakistan, Malaysia, and Indonesia. Sardar interviews Muslims with widely varying political leanings--including Pakistan's President Perez Musharraf, other government leaders, women's rights activists, and a cleric who promotes an extremely conservative form of Sharia
Title from container
Camera and sound, Kees t'Hooft ; film editor, John Kerry ; executive producer, iona Stourton
Presented by Ziauddin Sardar
Keywords: Islam -- Social aspects; Sociology, Islamic; Islam and politics; Islamic fundamentalism